De novo assembly and analysis of energy cane transcripts for sugarcane smut disease studies - Campos, Gabriela Romêro (2024)
Energy sugarcane has emerged as a significant resource of biomass for several countries, offering promising potential for the production of biofuels and other industrial products. To date, no genomes or transcriptomes of this crop have been reported, especially regarding interaction with the fungus Sporisorium scitamineum or other pathogens. The fungus S. scetamineum is one of the main pathogens that attack energy cane, causing significant impacts on yield. A good amount of information is available in the interaction between the pathogen and sugarcane, but much is needed to understand the interaction of the pathogen with energy cane. In order to shed some light in this interaction, two de novo assembly of the transcriptome of susceptible Vertix 1, and resistant Vertix 2 genotypes of energy cane was assembled with RNA-seq data obtained from energy cane buds 48 hours post inoculation (48hpi). Comparative analyses were conducted using both de novo transcriptomes, modern sugarcane cultivars, and related species. Additionally, a differential expression analysis was performed. We identified that despite energy cane presenting similarities with modern sugarcane cultivars and the species S. officinarum and as the defense responses are similar to those observed in interactions between sugarcane and S. scitamineum, it still has its own characteristics. These results bring important insights on the energy cane - S. scitamineum interaction.